2015
DOI: 10.1038/srep15184
|View full text |Cite|
|
Sign up to set email alerts
|

The conservation and signatures of lincRNAs in Marek’s disease of chicken

Abstract: Long intergenic non-coding RNAs (lincRNAs) associated with a number of cancers and other diseases have been identified in mammals, but they are still formidable to be comprehensively identified and characterized. Marek’s disease (MD) is a T cell lymphoma of chickens induced by Marek’s disease virus (MDV). Here, we used a MD chicken model to develop a precise pipeline for identifying lincRNAs and to determine the roles of lincRNAs in T cell tumorigenesis. More than 1,000 lincRNA loci were identified in chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 65 publications
(95 reference statements)
6
40
0
Order By: Relevance
“…These molecules can regulate gene expression much faster than proteins because the production of RNAs needs only transcription. A correlation of expression between lncRNAs and their neighboring protein-coding genes has been widely described in previous studies (Cabili et al, 2011;Guttman et al, 2011;He et al, 2015;Pauli et al, 2012;Peng et al, 2010) and observed in our study. The association of lncRNAs with chromatin-modifying complexes has been recognized as the reason for the coexpression (Khalil et al, 2009;Peng et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These molecules can regulate gene expression much faster than proteins because the production of RNAs needs only transcription. A correlation of expression between lncRNAs and their neighboring protein-coding genes has been widely described in previous studies (Cabili et al, 2011;Guttman et al, 2011;He et al, 2015;Pauli et al, 2012;Peng et al, 2010) and observed in our study. The association of lncRNAs with chromatin-modifying complexes has been recognized as the reason for the coexpression (Khalil et al, 2009;Peng et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…These lncRNAs were characterized by lower expression levels and shorter transcript lengths. These properties were also observed in other reported lncRNAs within the mammalian genome (Cabili et al, 2011;He et al, 2015;Peng et al, 2010;Ulitsky et al, 2011;Young et al, 2012;Boltana et al, 2016;Li et al, 2012a;Okazaki et al, 2002;Ulitsky et al, 2011). In addition, GO term enrichment analysis and KEGG pathway analysis indicated that various immune signaling pathways and antiviral responses may be regulated by cellular lncRNAs in response to PEDV infection.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations